Efektifitas Pijat Oketani dan Pijat Oksitosin dalam Meningkatkan Produksi Air Susu Ibu (ASI) - Fathiniah Anggraini; Erika; Ade Dilaruri (Universitas Bengkulu, 2022)
Breast care is done to improve blood circulation and prevent blockage of the milk ducts so as to expend milk. One of the breast treatments that can increase milk production is to do lactation massage, lactation massage types include oketani massage and oxytocin massage. Oketani massage is a breast massage that focuses on the areola and nipple area of the mother, this massage stimulates the strength of the pectoralis muscle to increase milk production so that the breasts become softer and more elastic. Oxytocin massage itself is a massage along the spine which is one solution to overcome the lack of smooth milk production. This study aims to determine the effectiveness of oketani massage and oxytocin massage in increasing the production of breast milk (ASI). This study uses quantitative research design with quasi experiment method, obtained samples using purposive sampling techniques as many as 34 respondents were divided into 2 groups of 17 respondents oketani massage and 17 respondents oxytocin massage. The measuring instrument used is an observation sheet of breast milk production volume with measurements before and after the action for 3 consecutive days. The statistical tests used are Wilcoxon test and Independent Sample T test. There is an effect of oketani massage and oxytocin massage on breast milk production with p value of 0.046 < ⑵ (0.05). The results of this study found that oketani massage and massage oxytocin effect in increasing breast milk production. This result is expected to be an alternative at the time of little milk production.